IDRC / G@W Peer Learning Event: Thoughts on the road to gender transformation - Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Presented at the IDRC/G@W Final Peer Learning Event of the 2019-2022 cohort of gender and CC programs, December 8, 2021.